Analysis of Biological Activities of Two Novel Metal (II) Complexes of Andrographis Paniculata Crude Extract - Mary Adelaide Oladipo; Ayodele Oluwabunmi Ojo; Kayode Taiwo Ishola (Biology, Medicine, & Natural Product Chemistry, 2023)
Many diseases in nature have led to the death of many young and old. Many bacteria have developed resistance to the available antibiotics on the market. And many drugs employed in treating many diseases such as diabetes mellitus are expensive and are not locally available. Therefore, in order to search for more effective, inexpensive, and locally available drugs, this study synthesized and investigated the biological activities of Andrographis paniculata crude extract and its Co (II) and Ni (II) complexes. The crude extract and synthesized complexes were characterized using a solubility test, Infrared, and Ultraviolet-Visible spectroscopic analysis. Their antibacterial potentials were investigated against two gram-negative bacteria (Escherichia coli,Staphylococcus aureus) and three gram-negative bacteria (Proteus, Klebsiella, Pseudomonas) while their antidiabetic activities were examined against ?-amylase and ?-glucosidase enzymes. Acarbose was employed as a standard drug. The crude extract and its metal complexes showed different degrees of solubility in the employed solvents. Infrared analysis suggested coordination of the crude extract to the metal ions through the oxygen donor atom while the formation of the complexes was affirmed through the occurrence of d-d transitions in the visible region of the metal complexes. The metal complexes were found to display more antibacterial activity than the crude extract. Co (II) and Ni (II) complexes of the crude extract were found to exhibit better activities against ?-amylase and ?-glucosidase enzymes, respectively than the crude extract and acarbose. It is concluded that the metal complexes could be considered potential antibacterial and antidiabetic agents.